Metabolic Interdependency of Th2 Cell-Mediated Type 2 Immunity and the Tumor Microenvironment - Schreiber, Simon; Hammers, Christoph M.; Kaasch, Achim J.; Schraven, Burkhart; Dudeck, Anne; Kahlfuss, Sascha (Frontiers in Immunology, 2021)
The function of T cells is critically dependent on their ability to generate metabolic building blocks to fulfil energy demands for proliferation and consecutive differentiation into various T helper (Th) cells. Th cells then have to adapt their metabolism to specific microenvironments within different organs during physiological and pathological immune responses. In this context, Th2 cells mediate immunity to parasites and are involved in the pathogenesis of allergic diseases including asthma, while CD8+ T cells and Th1 cells mediate immunity to viruses and tumors. Importantly, recent studies have investigated the metabolism of Th2 cells in more detail, while others have studied the influence of Th2 cell-mediated type 2 immunity on the tumor microenvironment (TME) and on tumor progression. We here review recent findings on the metabolism of Th2 cells and discuss how Th2 cells contribute to antitumor immunity. Combining the evidence from both types of studies, we provide here for the first time a perspective on how the energy metabolism of Th2 cells and the TME interact. Finally, we elaborate how a more detailed understanding of the unique metabolic interdependency between Th2 cells and the TME could reveal novel avenues for the development of immunotherapies in treating cancer.